2009
DOI: 10.4314/jae.v12i1.47027
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Farmers’ Access to and Perception of Extension Service Delivery in Borno State, Nigeria

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…For example, a farmer will be able to search for new improved seeds as they know the importance of using them. Moreover, education increases farmers' ability especially in making decisions for seeking demand-driven extension services because they understand well their needs [25] and [19] explained that educated farmers can search for new opportunities in agriculture that fit their needs to improve their agricultural production. In terms of marital status, the majority of respondents (76.7%) were married while 23.3% were not.…”
Section: Independent Variable Dependent Variablementioning
confidence: 99%
“…For example, a farmer will be able to search for new improved seeds as they know the importance of using them. Moreover, education increases farmers' ability especially in making decisions for seeking demand-driven extension services because they understand well their needs [25] and [19] explained that educated farmers can search for new opportunities in agriculture that fit their needs to improve their agricultural production. In terms of marital status, the majority of respondents (76.7%) were married while 23.3% were not.…”
Section: Independent Variable Dependent Variablementioning
confidence: 99%
“…This finding is line with Bose (2018) who reported that irrigated vegetable farmers adopted improved seed due to high yield and early maturity. Farmers tend to use a technology or practice to the extent that they derive benefits from it, while they reject or discontinue the use of a technology when they feel that the package is no longer performing as it used to be or is not what it is expected (Idrisa and Ogunbameru 2008;Abdulhamid et al, 2018).…”
Section: Technologies/practices Adopted In the Study Areamentioning
confidence: 99%